Aggregation-induced emission enhancement (AIEE)-active boron-difluoride dyes with reversible mechanochromic fluorescence. Issue 61 (4th November 2019) - Yan, Xiaojing; Zhu, Pengcheng; Zhou, Zhiguo; Yang, Hong; Lan, Haichuang; Xiao, Shuzhang
Abstract : A class of AIEE-active mechanochromic boron-difluorides were reported, and the mechanochromism was ascribed to the transition between H(J)-aggregation with loose molecular packing and J-aggregation with intense intermolecular interactions. Abstract : A novel class of solid-emissive boron-difluoride derivatives, using phenanthrenequinone hydrazone as ligands, were designed and efficiently synthesized. These dyes exhibit weak fluorescence in dilute solutions, but much higher fluorescence efficiency in aggregate states with a large stokes shift (over 70 nm) due to the their aggregation-induced emission enhancement (AIEE) characteristics. According to their photophysical properties and X-ray single crystal structure analysis, the AIEE was ascribed to the H(J)-aggregate formation aided by multiple intermolecular interactions to restrict intramolecular motion in the solid state. Moreover, their solid emissions could be reversibly tuned between "on" and "off" by mechanical grinding and recrystallization, due to the stacking model transition between H(J)-aggregation with loose molecular packing and J-aggregation with intense intermolecular interactions.